Expert System of Text Mining to Analyze Student Interaction in FTKI UNAS Online Lectures: Expert System of Text Mining to Analyze Student Interaction in FTKI UNAS Online Lectures - Novialdy Novialdy; Ucuk Darussalam; Ben Rahman (Jurnal Mantik, 2020)
Interactivity is the student activities or relationships between students with anything related to the course, his example by attending a class attendance responds directly at the appointed hour. What is meant here is the liveliness activities interactivity of students to answer the questions that exist in the online lecture forum, whether he is copying and pasting answers with other students or not. The number of student answers archives make web manager can not judge whether the student was copying and pasting the answer to her or not. Therefore we need a system that can provide a connection weights to archives word answers and calculates similarities between students answer word. To analyze the data from these students, writers manipulate the data using text mining. This research using tf-idf method cosine similarity, the parameters used are folding case, tokenizing, stopwords and stemming. The results of this study are that have a common answer to answer other students not considered effective in the online lectures, corresponding similarity weight percentage of statutes that have been determined.